CULTURAL PECULIARITIES IN TRANSLATION OF COLLOQUIAL VOCABULARY - Khafizova, Alsu A.; Antonova, Natalia V. (Gênero & Direito, 2019)
The present article studies peculiarities of colloquial vocabulary of English, Russian and French languages on the material of fictional texts and their translation, particularly works by S. Maugham and their translation into Russian and French. Special attention is paid to the problem of preserving stylistic component when translating from one language into another. Since the languages demonstrate their own specific features in the aspect of word choice determined by cultural nature, development of functional styles and peculiarities of linguistic and stylistic norms, translators have to face certain difficulties when transferring the source text into another language. One of the problems in this aspect is that translator has to find not only corresponding lexical or phraseological units to preserve semantic components of the original, but also follow the stylistic mode of the text and at the same time do not shift away from stylistic norms of the target language. The article shows how translators cope with this problem and try to solve both tasks.